The Treaty of Trianon and the Hungarian Post-war Settlement in the Eyes of the British - Cora, Zoltán; Papp, Erik; Forrai, Dorottya (AMERICANA E-journal of American Studies in Hungary, 2020)
British foreign policy examined Hungary’s role with respect to its effect on the European power-balance: it judged Hungary favourably as long as it was part of the Austro-Hungarian Monarchy, but, as Hungarian separatist ambitions grew stronger, the country was treated as a threat The paper looks at how the members of the British delegation at the Paris Peace Conference saw differently the way through which the maintenance of the above mentioned power balance could have been reached. Moreover, it is also scrutinised how various interest groups could exercise considerable impact on the outcome of the negotiations. On the one hand, Arthur Balfour, head of the British Foreign Office, thought that a long-term peace was possible only by strengthening the new, winner nation states, whose tasks were to hinder further German expansion towards the Balkans, and Bolshevism towards Europe. On the other hand, David Lloyd George, head of the British Cabinet, was on the opinion that only the extension of the Wilsonian Principles on the loser states could bring enduring peace in Europe. This study also investigates to what extent utilizing the nationalist movements proved to be effective tactics for the Entente Powers in reaching their war aims. Namely, the Entente proclaimed independence for the nationalities and a just settlement, but at the same time, they tried to comply with the secret covenants concluded during the war. These secret agreements did not take nationalist interests into consideration at all, and they meant specifically unjust arrangement to Hungary. Consequently, the paper argues that the Trianon Treaty was not only the result of political instability in Hungary and the Carpathian Basin in general as well as the validation of the Great Powers’ political interests on the continent, which proposed to impede German expansion and Russian Bolshevism, but also the result of the more effective propaganda activity of the anti-Hungarian group of British political activists and their international network led by Wickham Steed and Seton-Watson.